Food Symbolism and Traumatic Confinement in "We Have Always Lived in the Castle" - Muñoz González, Esther (Complutense Journal of English Studies, 2018)
We Have Always Lived in the Castle (1962) is a contemporary Gothic Novel in which women appear as both villains and victims, subverting the traditional characterization of women in classic Gothic Fiction. The apparently innocent and selfless Constance and the young Mary Kate live isolated and absolutely dedicated to housewifery. Due to the recurrent presence of food in the novel and drawn by the significance of its omnipresence, the purpose of this article is to discuss the symbolic meaning of food based on a cultural approach and how the characters’ relationship with food marks their social class, power position, anxieties, fears and desires within and outside the family.